Electronics for Embedded Systems - Bindal, Ahmet (Springer, 2017)
This book is written for young professionals, undergraduate and graduate students who have a background in basic circuit theory and want to learn about the circuits used in printed circuit boards and embedded systems. My teaching method in this textbook caters towards a lot of schematics, block diagrams and examples at the expense of text because I believe in engineers are “shape-oriented” people and learn from figures, charts and diagrams. The book has nine chapters. Chapter 1 analyzes the first-order passive RC and RL circuits and the second-order passive RLC circuits encountered in all Printed Circuit Boards (PCB). The general understanding of passive circuits also establishes a vital background for more complex circuits that contain active elements such as diodes and transistors. Chapter 2 reviews rectifier diodes, light emitting diodes, Zener diodes and explains simple circuits incorporating them. This chapter is also a review chapter for bipolar transistors, specifically NPN transistors, and discusses the circuit behavior and the conditions that lead to the NPN bipolar transistor in cut-off, active and saturation regions. Chapter 3 explains the N-channel and the P-channel MOS transistors, their current-voltage characteristics and CMOS gates, and then discusses the proper circuit design techniques that lead to transistor sizing in CMOS to meet design requirements prior to simulation. Chapter 4 starts with Transistor-Transistor-Logic (TTL), explains the circuit operation of a TTL inverter, its logic levels and fan-out limit. However, the emphasis of this chapter is more about the CMOS-TTL interface and the various circuits used at the interface for successful logic translation. Sensors and preliminary sensor physics are given in Chapter 5. The most common sensors such as thermocouple, photo-diode and photo-detector, Hall-effect device and piezoelectric sensors are discussed in this chapter. Chapter 6 examines the operational amplifiers and low-frequency operation amplifier circuits used for sensor output amplification. Voltage and trans-resistance amplifiers, analog comparators, Schmitt triggers, square waveform generators are included in this chapter. Chapter 7 reviews the theory behind data converters such as analog-to-digital converters (ADC) and digital-to-analog converters (DAC). Many different types of ADC designs, such as flash, ramp and successive approximation are explained in this chapter with numerical examples. The weighted adder-type and ladder-type DAC designs are also shown in this chapter.